Περιεκτικότητα πρωτεΐνης στον καρπό πληθυσμών βρώμης που καλλιεργήθηκαν στην Κύπρο - Μουσικός, Παναγιώτης (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
In the present study the quality of 73 European oat seed populations, in majority from Greece, was investigated. The different populations were cultivated in Cyprus (Paphos area) during the period 2013-2014. Protein content was determined as well as the weight of seeds, the percentage of gran hulls and the moister content for each population. The results obtained were in accordance with previous studies using the same oat populations. The protein content of the tested oat populations ranged from 7.39% to 13.86% (average of 10.62% on dry matter basis), the grain hulls ranged from 23% to 35% (average of 30%), the weight of oat seeds from 0,021 gr to 0,062 gr (average of 0,36 gr), while the moisture content ranged from 6.14% to 14.22% (average of 9.81%). Furthermore, the use of oat grains in ruminant diets was also reviewed in the present study with encouraging conclusions regarding the use of the oat seeds.
Keywords: Oat varieties; Crude protein; Ruminant; Πληθυσμοί βρώμης; Πρωτεΐνη; Μηρυκαστικά